A Retrospective Analysis of Safety and Efficacy of XEN 45 Microstent Combined Cataract Surgery in Open-Angle Glaucoma over 24 Months - Sevgi Subaşı; Nurşen Yüksel; Fevzi Özer; Büşra Yılmaz Tugan; Dilara Pirhan (Türk Oftalmoloji Dergisi, 2021)

(untitled)
Objectives:To evaluate the effect on intraocular pressure (IOP) reduction and safety of ab interno gelatin microstent (XEN 45 Gel Stent; Aquesys, Inc, Aliso Viejo, CA, USA) microincisional glaucoma/cataract surgery in open-angle glaucoma (OAG).Materials and Methods:In this retrospective study, 30 eyes of 25 patients with OAG which underwent XEN 45 implantation combined with simultaneous phacoemulsification were clinically evaluated. Clinical outcomes analyzed included IOP, percent of IOP reduction, medication use, complications, best corrected visual acuity, and surgical outcomes at 24-month follow-up.Results:After the XEN 45 combined cataract surgery procedure, IOP dropped from 20.37±4.80 mmHg with a mean of 3.07±1.04 medication classes preoperatively to 14.83±1.91 mmHg with a mean of 0.94±1.11 medication classes at 24 months (p=0.001 for both). At 24 months, 55.6% of patients had IOP ≤18 mmHg without medication, 94.4% of patients had IOP ≤18 mmHg with or without medication, and 61.1% of patients reached ≥20% IOP reduction from baseline.Conclusion:XEN 45 is an effective minimally invasive surgical treatment for OAG with significant reduction in IOP and glaucoma medications and minimal complications in long-term follow-up.